Enhancing stoichiometry learning through youtube video-lists - Segala, Maximiliano (2025)
Stoichiometry is generally seen by students as one of the most difficult subjects to understand. This has been observed through our experience as high school teachers in public and private schools in Brazil. We have realized that new teaching resources are needed to minimize such difficulties, assisting both the teaching and learning process. Teaching materials produced by teachers themselves must be more efficient, as they portray the school reality itself, making teaching, in a certain way, personalized. In addition, these classroom materials must be made available online in order to serve the largest possible number of students. This work involves the creation of an educational product, presented as an audiovisual resource, as it brings very efficient elements to the teaching and learning process, such as movement, colors and sounds. In the Programa de Mestrado Profissional em Química em Rede Nacional (PROFQUI) of the Universidade Federal do Rio Grande do Sul (UFRGS), we created a YouTube channel, which presents the solution of stoichiometry exercises of increasing difficulty level. The videos were recorded on a smartphone and edited using free software, in a process that can be reproduced by any teacher with internet access. Thus, our work mainly aims to develop such materials to serve as inspiration for teachers to create their own classroom materials, based on the school reality in which they are inserted. Questionnaires were applied before and after the use of the material and the data collected were analyzed from the perspective of Bardin's content analysis. The material presented excellent results in terms of improving the learning of stoichiometry, results verified through a pre- and post-test, as well as a questionnaire on the students' impression of the material produced.